2022
DOI: 10.3389/fphys.2022.792292
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Aerobic Exercise Improving Vascular Remodeling in Hypertension

Abstract: The treatment and prevention of hypertension has been a worldwide medical challenge. The key pathological hallmark of hypertension is altered arterial vascular structure and function, i.e., increased peripheral vascular resistance due to vascular remodeling. The aim of this review is to elucidate the molecular mechanisms of vascular remodeling in hypertension and the protective mechanisms of aerobic exercise against vascular remodeling during the pathological process of hypertension. The main focus is on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Lifestyle modifications such as alteration of dietary habits and regular exercise, known as non-pharmacological interventions, are seen as beneficial approach in the management and delay of hypertension and hypertension-related pathologies. Although resveratrol supplementation and regular exercise are described to have positive effects in hypertension due to their antioxidant and anti-inflammatory properties [33,34], their effects on hepatic changes in the hypertensive state have not been comparatively examined.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modifications such as alteration of dietary habits and regular exercise, known as non-pharmacological interventions, are seen as beneficial approach in the management and delay of hypertension and hypertension-related pathologies. Although resveratrol supplementation and regular exercise are described to have positive effects in hypertension due to their antioxidant and anti-inflammatory properties [33,34], their effects on hepatic changes in the hypertensive state have not been comparatively examined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its association with exercise and even larger effects on neuroplasticity suggests that part of it is due to the exercise itself. There is a significant amount of evidence showing the influence of regular AE on molecular process changes (Brandão et al., 2020; Farrell and Turgeon, 2021; Song et al., 2022), increasing the levels of neurotrophic factors, such as BDNF, which mediates neuroplasticity (Walsh and Tschakovsky, 2018). This protein was shown to increase after single sessions of exercise, but with potentiated effects when preceded by regular exercises (Walsh and Tschakovsky, 2018), which may explain why the study with the longest period of follow‐up was the most significant one.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of 391 randomized-controlled, trial intervention studies (43) showed that exercise has an effect comparable to that of antihypertensive medication in lowering SBP in hypertensive populations. Positive effects of exercise on blood pressure are related to vascular system remodeling and enhanced cardiac function (65,66). Owing to the limitation of the study population, who dwelled in the same geological area, and a limited number of participants who exercised regularly, this study could not appropriately assess the modifying effect of exercise on the relationship between skeletal muscle mass and hypertension.…”
Section: Discussionmentioning
confidence: 99%